How to Improve Safety Commitment: A Case Study on a Plastic Manufacturer in East Java - Suherdin Suherdin; Noeroel Widajati; M. Bagus Qomaruddin (Universitas Airlangga, 2021)
Introduction: Every year, work accidents frequently occur at PT. X. The initial survey showed a lack of control and commitment to be the main problems. Commitment is the core of the implementation of Occupational Health and Safety (OHS). This study aims to determine the factors that can increase safety commitment of workers. Method: This study used a quantitative approach with a cross-sectional design. In this study, the independent variables were age, gender, years of service, education level, safety motivation, management of safety commitment, safety communication, and social support. Meanwhile, the dependent variable was the safety commitment. 78 workers were selected using a simple random sampling technique from a population of 395 workers. Questionnaires were used to collect data. Data analysis used a multinomial logistic regression test. Results: 64.1% of workers were aged 41-51 years old, 56.4% were females, 82.0% had >10 years of service, 75.6% had a secondary education level, 56.4% had high safety motivation, 57.7% assessed management commitment to safety as low, 59.0% assessed safety communication as less, 52.6% had high social support, and 37.2% tended to have continuous safety commitment. Characteristics of workers (age, gender, years of service, education level), safety motivation, and social support did not affect safety commitment. Meanwhile, management commitment to safety (p=0.004) and safety communication (p=0.014) affected safety commitment of workers. Conclusion: The way to increase workers' commitment to safety is to increase the company's commitment to OHS and improve safety communication efforts.Keywords: management commitment to safety, safety commitment, safety communication